Peran Satuan Polisi Pamong Praja (Satpol PP) dalam Menertibkan Bangunan Liar di Kecamatan Bagan Sinembah Kabupaten Rokan Hilir Provinsi Riau - Agustinus Pandiangan; Abdul Kadir; Yurial Arief Lubis (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2023)
This research is aimed to know the role of Public Order Agency in curbing illegal buildings especially for regulation, institution, and human resources in the implementation of that role. The problems on this research would discuss about: 1) The role of Public Order Agency in curbing illegal buildings in Bagan Sinembah, Rokan Hilir, Riau. 2) The factors which became an obstacle for Public Order Agency in curbing illegal buildings in Bagan Sinembah,  Rokan  Hilir,  Riau.  This research  used  qualitative method  as a  data analysis method in the office of Public Order Agency. The source of data on this research is the head of  Public Order Agency, the head of public order and a public comfort, the member of Public Order Agency, sub-district office employee of Bagan Sinembah and the society affected by the enforcement. The data were collected based on doing an interview and documentation. The result  of  this  research  showed  that  the  role  of  Public  Order  Agency  in  curbing  illegal buildings in Bagan Sinembah, Rokan Hilir, Riau started from socialization, data collection, an appeal, until the control was done.